2006
DOI: 10.1007/s10151-006-0266-1
|View full text |Cite
|
Sign up to set email alerts
|

Is mechanical bowel preparation mandatory for left-sided colonic anastomosis? Results of a prospective randomized trial

Abstract: These results suggest that elective left-sided anastomosis may be safely performed without mechanical preparation. Multicenter studies to test the reproducibility of these results are required, to support a change in this time-honored practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 16 publications
3
63
0
4
Order By: Relevance
“…There have been numerous studies focused on the risks of bowel preparation and their appropriateness and numerous studies have found no evidence that mechanical bowel preparation has an effect on anastomotic leak. [100][101][102] Bearing this in mind, recommendations have been made to avoid mechanical bowel prepping patients due to concerns regarding patient satisfaction, potential electrolyte disturbances, and potential risk of Clostridium difficile infection.…”
mentioning
confidence: 99%
“…There have been numerous studies focused on the risks of bowel preparation and their appropriateness and numerous studies have found no evidence that mechanical bowel preparation has an effect on anastomotic leak. [100][101][102] Bearing this in mind, recommendations have been made to avoid mechanical bowel prepping patients due to concerns regarding patient satisfaction, potential electrolyte disturbances, and potential risk of Clostridium difficile infection.…”
mentioning
confidence: 99%
“…Although the bowel preparation facilitate the achievement of the surgical technique, making the operation less inconvenient, many other factors put this conduct in question, since there is evidence to prove the bacterial translocation to mesenteric lymph nodes when done the preparation 7,16 , higher peritoneal contamination during surgery due to liquid stool, 8, and gastrointestinal discomfort, involving 7,14 diarrhea, bloating and nausea. There are also systemic consequences, such as hydroelectrolytic disturbances of cardiac risk in cardiac patients 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Zmora et al 16 evaluated the results of a prospective randomized trial questioning the mechanical bowel preparation for anastomosis of the left colon; 249 patients were analyzed, 120 with preparation and 129 not, with higher rates of anastomotic leak and 4,2%x2,3% and 1,6%x0,7% respectively, favoring the non-preparation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations